2020
DOI: 10.1136/jitc-2020-000958
|View full text |Cite|
|
Sign up to set email alerts
|

Immune checkpoint inhibitor-associated celiac disease

Abstract: BackgroundRare cases of immune checkpoint inhibitor (ICI)-associated celiac disease (ICI-CeD) have been reported, suggesting that disruption of tolerance mechanisms by ICIs can unmask celiac disease (CeD). This study aims to characterize the clinicopathological and immunophenotypic features of ICI-CeD in comparison to ICI-associated duodenitis (ICI-Duo) and usual CeD.MethodsA medical and pathological records search between 2015 and 2019 identified eight cases of ICI-CeD, confirmed by tTG-IgA. Nine cases of ICI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 34 publications
1
64
0
Order By: Relevance
“…Among the eight patients who presented with new-onset celiac disease after ICI, improvement in signs and symptoms (including Open access down-trending tTG IgA) was observed after a gluten-free diet was implemented as the sole intervention. 83…”
Section: Diarrhea and Colitismentioning
confidence: 99%
“…Among the eight patients who presented with new-onset celiac disease after ICI, improvement in signs and symptoms (including Open access down-trending tTG IgA) was observed after a gluten-free diet was implemented as the sole intervention. 83…”
Section: Diarrhea and Colitismentioning
confidence: 99%
“…Badran et al in their study identified patients who developed ICI-induced celiac disease [ 14 ]. Among the patients who developed celiac disease with the ICIs, two had NSCLC, one had extraskeletal myxoid chondrosarcoma, and one had squamous cell carcinoma of the tonsil [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Badran et al in their study identified patients who developed ICI-induced celiac disease [ 14 ]. Among the patients who developed celiac disease with the ICIs, two had NSCLC, one had extraskeletal myxoid chondrosarcoma, and one had squamous cell carcinoma of the tonsil [ 14 ]. Furthermore, the responsiveness of ICI-induced celiac disease to gluten-free diet alone in five (62%) out of the eight cases illustrated that gluten is an important antigen driving ICI-induced celiac disease, similar to standard celiac disease [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, true coeliac disease can manifest in patients receiving ICIs. 98,99 These cases are associated with elevated tTG levels, and show a histological response to a GFD.…”
Section: Ici-associated Duodenitismentioning
confidence: 99%
“…Eosinophil and neutrophil infiltration are more prominent than ever seen in coeliac disease (Figure 7). In addition, true coeliac disease can manifest in patients receiving ICIs 98,99 . These cases are associated with elevated tTG levels, and show a histological response to a GFD.…”
Section: Malabsorption Secondary To Mucosal Inflammationmentioning
confidence: 99%